Gender and authorship of publications from Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) - Jeyapalan, Asumthia S.; Brown, Stephanie R.; Gaspers, Mary G.; Haliani, Brittany; Kudchadkar, Sapna R.; Rowan, Courtney M.; Gertz, Shira J. (Frontiers in Pediatrics, 2023)
Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) is a network fostering clinical research to optimize care in critically ill children. We aim to examine the efforts of PALISI to increase gender parity in research as evidenced by authorship. The first and senior authors of all published PALISI articles from 2002 - 2021 were analyzed for gender of presentation. Funding sources, impact factor, professional role, and location were extracted. We identified 303 articles, 61 published from 2002-2011 and 242 from 2012-2021. There were 302 first authors representing 188 unique individuals with 283 senior authors representing 119 unique individuals. Over half (55.6%, n=168) of the first authors were women. More women were first authors from 2012-2021 (n=145, 60.2%) as compared to 2002-2011 [37.7%, n=23, OR= 2.50 (95% CI: 1.40, 4.45, p=0.002)]. Senior authors were 36.0% (n=102) women with no change over time. Women senior authors had a higher proportion of women first authors (67.7% vs 32.4%, p=0.017). No gender differences were noted based on type of article or impact factor. A majority of authors wrote from institutions in the United States. Women had comparatively more NIH and CDC funding but less from foundations and AHRQ. PALISI has had first authorship by women increase over time such that it now exceeds both the proportion of women pediatric intensivists and women first authors in critical care publications. Senior women authorship has been stagnant. A multifactorial approach is needed by individuals, institutions, networks and journals to bring senior women authors to parity.